Early occurrences of the use of smalt and shell gold in the Madonna of Humility by Jacopo Bellini at the beginning of the fifteenth century - Eveno, Myriam; Ravaud, Elisabeth (European physical journal plus, 2021)
Jacopo Bellini’s Madonna of Humility painted around 1430-40 is a Venetian painting from the Louvre Museum (Paris). Jacopo Bellini, father of well-known Giovanni and Gentile Bellini, is the founder of a dynasty of Venetian painters (Dunkerton and Spring in Natl Gallery Tech Bull 39:4–25, 2018; Eisler in Abrams, Inc, New York, 1989). Although the British Museum and the Louvre Museum keep two important drawing books, very few paintings from Jacopo still exist today (Eisler in Abrams, Inc, New York, 1989). The study of the Madonna of Humility provided new data about early fifteenth century Venice painting practices, and in particular, the investigations brought to light two major points: the use of a still unusual gilding technique and one of the earliest occurrences of smalt in a painting. This study analyzed the composition of the pigments and gilding via stereomicroscopy and macroscopic X-ray fluorescence imaging. Scanning electron microscopy with energy-dispersive spectroscopy, Fourier transform infrared spectroscopy imaging, and X-ray absorption spectroscopy were performed on embedded micro-samples. Three gilding techniques have been identified. Besides the more common water and mordant gilding, the painting provides a very early example of shell gold use that could be investigated in depth. Unexpected smalt was identified in an underlayer of the Virgin’s dress and in the sky, here mixed with lapis lazuli, as in the most first known occurrences (Stege in Zeitschrift für Kunsttechnologie und Konservierung ZKK 18:121–142, 2004). Additionally, the elemental composition of the smalt particles showed unusual elements, such as copper, tin, and lead. The detailed study of the composition allows getting new insights into the origin of the cobalt ore and the way the glass pigment was prepared in this early recipe.